Kiln sites of the fourteenth-twentieth-century Julfar ware pottery industry in Ras al-Khaimah, UAE - Mitsuishi, Gen; Kennet, Derek; Hawker, Ron; Szuchman, Jeffrey (Proceedings of the Seminar for Arabian Studies, 2013)
This paper presents a summary of the results of a study of four kiln sites of Julfar ware, a coarse ware that was produced in the Shimal area of Ras al-Khaimah (UAE) close to the historical site of Julfar between the fourteenth and twentieth centuries. The paper presents and analyses surface assemblages of pottery that were collected from each of the kiln sites. The kiln sites are described and an outline of the typology that was developed to catalogue the ceramic assemblage is presented. A seriation of the assemblage demonstrates a relative chronology of the four sites that can be linked to an absolute chronology using external data. Using the range of types at each kiln site as a proxy for the intensity of production suggests a peak of production in the fifteenth to sixteenth century contemporary with the main phase of occupation at historic Julfar, and contemporary with the widest distribution of Julfar ware around the western Indian Ocean. Analysis of the coefficient of variation of rim diameters from the most common types from three of the sites suggests related changes in the organization of production.